Echocardiography in shock - Chew, Michelle S; Aissaoui, Nadia; Balik, Martin (Current opinion in critical care, 2023)
PURPOSE OF REVIEW: The aim of this study was to illustrate the varying roles of echocardiography in all phases of shock ranging from a rapid, diagnostic tool at the bedside, to a tool for monitoring the adequacy and effects of shock treatment and finally for identification of patients suitable for de-escalation of therapy. RECENT FINDINGS: Echocardiography has become an indispensable tool for establishing diagnosis in patients with shock. It is also important for assessing the adequacy of treatment such as fluid resuscitation, vasopressors and inotropes by providing integrated information on cardiac contractility and systemic flow conditions, particularly when used in conjunction with other methods of advanced haemodynamic monitoring. Apart from a traditional, diagnostic role, it may be used as an advanced, albeit intermittent, monitoring tool. Examples include the assessment of heart-lung interactions in mechanically ventilated patients, fluid responsiveness, vasopressor adequacy, preload dependence in ventilator-induced pulmonary oedema and indications for and monitoring during extracorporeal life support. Emerging studies also illustrate the role of echocardiography in de-escalation of shock treatment. SUMMARY: This study provides the reader with a structured review on the uses of echocardiography in all phases of shock treatment.
Keywords: echokardiografie; Hemodynamics; vazokonstriktory; hemodynamika; srdce; Heart; lidé; tekutinová terapie; Vasoconstrictor Agents; Shock; šok; Fluid Therapy; Echocardiography; Humans